PENGEMBANGAN MANAJEMEN DATA ELEKTRONIK PAUD DI PAC AISYIYAH KECAMATAN TINGKIR, SALATIGA - Yusuf Sulistyo Nugroho (WARTA LPM, 2015)
PAUD Aisyiyah 3 Salatiga consists of two (2) institutions namely kindergarten (TK) Aisyiyah 3 and Playgroup (KB) Aisyiyah 3 as one of the educational institutions in Salatiga. However, the processing of the academic data still established conventionally, in which the data is only written in a book. This is certainly unable to prevent the repetition of the data that is recorded. Repetition of data can lead to inefficient bookkeeping and frequent errors relationships among the data. In addition, the book is stored in filing cabinets that affect the occurrence of difficulties in the search for the necessary data at any time. This service activity carried out in order to help PAUD Aisyiyah 3 Salatiga perform academic data management through the website. It is considered as data management using the internet media is a means of managing data that can be done easily, quickly and cheaper cost. Thus, the output is a website for the education institutions PAUD Aisyiyah 3 Salatiga. The activity carried out with the first step is creating a management information system of school academic data. The system is made using a CMS with the programming language is PHP and Javascript. The information system is then hosted online. The second stage is conducting training for the school teachers. With this training, participants are expected to take advantage of academic data management information system optimally to manage the data of academic school. The result is a web-based academic data management information system at www.paudaba3salatiga.com. The information system is made with two types of users, namely as an admin user that has full access rights, and ordinary users with limited privileges. This system can be used to manage the data of teachers, students, parents / guardians of students, classes, inventory, learning activities, and assessment activities of the students. Meanwhile, the training result shows some problems, such as lack of Internet connections in schools, and the limited ability of teachers in the terms of information technology. Therefore, the team will continue to monitor the use of the information systems